2019
DOI: 10.1055/s-0039-1700837
|View full text |Cite
|
Sign up to set email alerts
|

Improved Patient Satisfaction following Robotic-Assisted Total Knee Arthroplasty

Abstract: Approximately 20% of the patients are dissatisfied with their total knee arthroplasty (TKA). Computer technology has been introduced for TKA to provide real time intraoperative information on limb alignment and exact flexion/extension gap measurements. The purpose of this study was to determine if patient satisfaction could be improved with the use of robotic-assisted (RA) technology following primary TKA. A total of 120 consecutive patients undergoing RA-TKA with real time intraoperative alignment and gap bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 26 publications
(40 reference statements)
6
67
0
Order By: Relevance
“…Bhimani et al [4] 2020 RATKA: to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps Unknown which technique and which reference alignment was utilised mTKA: A gap balancing technique was utilized using a ligamentous tensioning device with the extension gap balanced followed by balancing the flexion gap after release of the posterior cruciate ligament Gap balancing techniques utilised Kayani et al [18] 2018 mTKA utilised a measured resection technique aligned to the mechanical axis RATKA utilised dynamic referencing to achieve equal gaps throughout the range of motion, utilising gap balancing and kinematic alignment techniques Kayani et al [19] 2018 RATKA: intraoperative dynamic gap balancing techniques were used with kinematic alignment assessed through the arc of motion, and enabled fine tuning of implant positioning based on laxity of the soft tissue envelope, within 2 mm of the planned bone resection Utilised restricted kinematic alignment techniques mTKA: measured resection and mechanical alignment as reference Mahoney et al [28] 2020 Both RATKA and mTKA utilised mechanical alignment as reference for all except nine cases of two centers that were targeted within ± 3 degrees Marchand et al [30] 2017 RATKA: the prosthesis was manipulated allowing for optimal balancing and realignment. The knee was brought into extension, and alignment was checked with the robotic-assisted device both in extension and at 90 degrees of flexion No mention if mechanical/kinematic alignment was utilised to check the knee in extension mTKA: measured resection techniques used with mechanical alignment as reference Smith et al [49] 2019 RATKA: equal gap measurements within 1 mm between the flexion and extension gaps and the medial and lateral gaps, keeping limb alignment within 3 degrees of the mechanical axis and use the bone cuts to balance gaps instead of soft tissue releases unless the target fell out of 3 degrees window, at which point a combination of bone cuts and soft tissue releases was utilized to achieve balanced gaps within 1 mm Restricted kinematic alignment and gap balancing techniques mTKA: Mechanical alignment and measured resection techniques utilised Sultan et al [51] 2019 RATKA: Intraoperative adjustments to the plan were performed to determine ideal component placement for a balanced knee. Ligament balancing was assessed following resections and after trialing mTKA was performed using a standard technique No mention of measured resection or gap balancing techniques nor how mechanical / kinematic alignment was achieved [19] 2018 MUA mTKA 0 vs RATKA 0 Superficial and deep infections mTKA 0 vs RATKA 0 Wound dehiscence mTKA, 1 (distal part of the midline incision) vs RATKA group 1 (incision for the proximal tibial registration pins), all recovered with regular dressings and prophylactic oral antibiotics Time to discharge (hrs), median (IQR) mTKA 105.0 (IQR 98.0-126.0) vs RATKA 77.0 (IQR 74.0-81.0), p < 0.001 Post-operative pain score -day 3, mean (range) mTKA 4.5 (2.0-7.0) vs RATKA 2.6 (1.0-5.0), p < 0.001 Kayani et al [20] 2019 MUA mTKA 0 vs RATKA 0 Superficial and deep infections mTKA 0 vs RATKA 0 Wound dehiscence mTKA, 1 (distal part of the midline incision) vs RATKA group 1 (incision for the proximal tibial registration pins), all recovered with regular dressings and prophylactic oral antibiotics…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bhimani et al [4] 2020 RATKA: to achieve the desired bone cuts and target limb alignment, along with symmetrically balanced flexion and extension gaps Unknown which technique and which reference alignment was utilised mTKA: A gap balancing technique was utilized using a ligamentous tensioning device with the extension gap balanced followed by balancing the flexion gap after release of the posterior cruciate ligament Gap balancing techniques utilised Kayani et al [18] 2018 mTKA utilised a measured resection technique aligned to the mechanical axis RATKA utilised dynamic referencing to achieve equal gaps throughout the range of motion, utilising gap balancing and kinematic alignment techniques Kayani et al [19] 2018 RATKA: intraoperative dynamic gap balancing techniques were used with kinematic alignment assessed through the arc of motion, and enabled fine tuning of implant positioning based on laxity of the soft tissue envelope, within 2 mm of the planned bone resection Utilised restricted kinematic alignment techniques mTKA: measured resection and mechanical alignment as reference Mahoney et al [28] 2020 Both RATKA and mTKA utilised mechanical alignment as reference for all except nine cases of two centers that were targeted within ± 3 degrees Marchand et al [30] 2017 RATKA: the prosthesis was manipulated allowing for optimal balancing and realignment. The knee was brought into extension, and alignment was checked with the robotic-assisted device both in extension and at 90 degrees of flexion No mention if mechanical/kinematic alignment was utilised to check the knee in extension mTKA: measured resection techniques used with mechanical alignment as reference Smith et al [49] 2019 RATKA: equal gap measurements within 1 mm between the flexion and extension gaps and the medial and lateral gaps, keeping limb alignment within 3 degrees of the mechanical axis and use the bone cuts to balance gaps instead of soft tissue releases unless the target fell out of 3 degrees window, at which point a combination of bone cuts and soft tissue releases was utilized to achieve balanced gaps within 1 mm Restricted kinematic alignment and gap balancing techniques mTKA: Mechanical alignment and measured resection techniques utilised Sultan et al [51] 2019 RATKA: Intraoperative adjustments to the plan were performed to determine ideal component placement for a balanced knee. Ligament balancing was assessed following resections and after trialing mTKA was performed using a standard technique No mention of measured resection or gap balancing techniques nor how mechanical / kinematic alignment was achieved [19] 2018 MUA mTKA 0 vs RATKA 0 Superficial and deep infections mTKA 0 vs RATKA 0 Wound dehiscence mTKA, 1 (distal part of the midline incision) vs RATKA group 1 (incision for the proximal tibial registration pins), all recovered with regular dressings and prophylactic oral antibiotics Time to discharge (hrs), median (IQR) mTKA 105.0 (IQR 98.0-126.0) vs RATKA 77.0 (IQR 74.0-81.0), p < 0.001 Post-operative pain score -day 3, mean (range) mTKA 4.5 (2.0-7.0) vs RATKA 2.6 (1.0-5.0), p < 0.001 Kayani et al [20] 2019 MUA mTKA 0 vs RATKA 0 Superficial and deep infections mTKA 0 vs RATKA 0 Wound dehiscence mTKA, 1 (distal part of the midline incision) vs RATKA group 1 (incision for the proximal tibial registration pins), all recovered with regular dressings and prophylactic oral antibiotics…”
Section: Discussionmentioning
confidence: 99%
“…The three remaining studies, however, used different methods for their RATKA and mTKA groups, namely kinematic alignment Fig. 1 Complete PRISMA flow diagram showing the identification, screening, eligibility and inclusion process and gap balancing methods for RATKAs and measured resection methods for mTKAs [18,20,49].…”
Section: Knee Balancing and Alignment Techniques (Level Of Evidence: Fair)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kayani et al reported that image-based robotic-assisted TKA was associated with reduced bone and periarticular soft tissue injury compared with conventional TKA [ 95 ]. Several case-controlled studies assessed the short-term functional postoperative scores, with a maximum follow-up of 17 months, between robotic-assisted and conventional TKA, with inconclusive results [ 96 , 97 , 98 , 99 ]. More investigations at mid and long-term are necessary for the semiautonomous robotic-assisted system.…”
Section: Robotic-assisted Knee Arthroplastymentioning
confidence: 99%
“… 44 Additionally, the haptic feedback provided by these systems confers superior soft tissue protection compared to conventional TKA, which may explain the early functional benefits with these systems. 57 , 58 , 62 64 , 90 In contrast, these early functional gains were lacking in older systems, where a much larger surgical exposure was required to prevent iatrogenic soft tissue injury. 14 Long-term functional outcomes comparing these newer robotic systems with conventional techniques are still required.…”
Section: Discussionmentioning
confidence: 99%